DETERMINATION OF DESIGN INFORMATION SYSTEM CHECK MINE IN SURABAYA EAST NUSA SHIPPING COMPANY. - Juniarti, Ni Nyoman Swastika; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
PT Nusa Tenggara is one of shipping company deals with sea shipment for delivering goods in entire Indonesia region. So far, determination of the fast fee is only based on its mileage therefore all ships with the same route have the same fast fee. Meanwhile each ship has different operational cost though they are in the same route. This situation influences to the income of each ship. Based on the data ofÂ  ship income in 2013, it shows that the income can not cover operational cost of each ship. The offering solution is information system for determining fast fee by using variable costing methode and web based that can be able to determine fast fee or ship charter fee based on routes and ship used by the buyer. It has some main processes such as adding pre-operational ship data, counting the main cost of ship production, counting percentage of ROI per mile, counting percentage of markup per mile, and counting fast fee. After being tested, this application is able to help operational director giving information dealing with determining process of fast fee. Furthermore, it is also able to make bargaining process between director and agent charter faster so it can produce fast fee based on charter party.